Role of Ultrasound and computed tomography in assessment of abdominal lymphadenopathy and splenomegally in lymphomas - Mohson, Khaleel I.; Al-Hilli, Mohammed (Journal of the Faculty of Medicine Baghdad, 2016)
Background: lymph nodes involvement is the most common presentation of abdominal lymphoma; their diagnosis is based on variety of imaging modalities, histopathology of different areas of involvement and stage of the disease. Objective: to compare the value of abdominal ultrasound (US) and computed tomography (CT) scan in already diagnosed cases of lymphoma and evaluation of lymph nodes and splenic involvement in patients with proved lymphoma. Patients and methods: thirty patients with lymphoma were gathered from hematological unit in Baghdad teaching hospital retrospectively depending on their histopathology that revealed either Hodgkin lymphoma (HL) or non-Hodgkin lymphoma (NHL) and they were examined by ultrasound and CT scan of the abdomen, then were categorized according to the lymph nodes regions involvement. Results: the results showed that both ultrasound and CT are nearly equal in detecting upper abdominal adenopathy and splenic involvement, while CT is better than ultrasound in assessment of lower abdominal, mesenteric and para-iliac lymph nodes groups. Conclusion: our results are comparable to the earlier series and show improved detection of lymph nodes by new modality CT.